Behavioral Contracting With Adolescents and Their Families - Martin, Roger D. (Canadian Journal of Counselling and Psychotherapy, 2012)
Within the counsellor-as-teacher frame of reference, the concept of behavioral contracting is examined. Basic issues are developed and evaluated. An illustrative contract between an adolescent and his parents is presented.